The Game Is Good at the Top. (June 2018) - Segura, Jerome; Willner, Jonathan
Collegiate football may provide advertising for universities, attracting larger pools of applicants and leading to more academically qualified student bodies. Football may also build school spirit, reducing attrition and improving long-run graduation rates. This analysis uses data from 2001 to 2004 for available National Collegiate Athletic Association Division-1 institutions to examine the advertising and effectiveness effects of football. Using both general linear model and linear-in-means model estimation procedures, we find strong advertising and effectiveness effects for football in the full sample. Among schools fielding a football team, the impact of Football Bowl Subdivision and winning percentage is muddy; however, the advertising effect of bowl appearances is strong.